PENDEKATAN SAINTIFIK DALAM IMPLEMENTASI KURIKULUM 2013 BERDASARKAN KAJIAN TEORI PSIKOLOGI BELAJAR - Susilana, Rudi (Prodi Teknologi Pendidikan, 2014)
Abstract. The 2013 Curriculum offers a few new things, one of which is the emphasis on the application of the scientific approach. The scientific approach in 2013 Curriculum includes five core activities consisting of several activities as follows: observing, asking, doing, reasoning or associating, and communicating (drawing conclusion, presenting). This paper tries to describe the results of the theoretical studies of psychology of learning about activities developed in the scientific approach and formulate some conclusions that are expected to provide